OPTIMAL PORTOFOLIO FORMATION WITH SINGLE INDEX MODEL AND MARKOWITZ FOR COMPANIES LISTED ON SRI-KEHATI - Annisa Agustina; Prisila Damayanty Damayanty (Journal of Economic, Bussines and Accounting (COSTING), 2024)
ABSTRACT This research is a quantitative research that aims to determine the optimal portofolio stock formation in companies listed on the SRI-KEHATI Index consistently with the Single Index Model approach and the Markowitz Model. The samples obtained using the purposive sampling technique are 13 companies with the 2018-2021 period. The data analysis method used in this study is the Shapiro-Wilk Normality test and the Independent Sample t-test. The results showed that the Single Index Model formed 4 stocks, namely BBRI, PGAS, SMGR, and WIKA. Whereas the Markowitz Model produces 5 shares, namely BBNI, BBRI, BMRI, KLBF, and TLKM. The formed portofolio candidates have positive return and risk of optimal stock portofolios but have different results. keywords: Single Index Model, Model Markowitz, Optimal Portofolio